Integrating ICT in Teaching and Learning at School Level: A Systematic Review (Tribhuvan Journal, 2025)
Introduction: The effect of information and communication technology (ICT) integration in school education has continued to attract interest as a means of enhancing the effectiveness of student learning. However, as widely used as it is, there are still major gaps in how and how effectively ICT is applied across various settings. This paper will analyze the existing literature on the subject of integration of ICT in schools to understand the extent, the results and difficulties involved.Methods: The review was conducted according to PRISMA guidelines of systematic reviews. Google Scholar, Scopus, ERIC and Web of Science were searched to find articles published between 2015 and 2025, including the terms: ICT integration, school education, teaching and learning, and digital pedagogy. Empirical and review studies (at the school level) were eligible, and non-English publications, abstracts of conferences, reports, and editorials were excluded. Among 1,245 records first located, 245 were eliminated as duplicates, 1,000 were filtered by title and abstract and 180 full texts analyzed. A total of 60 studies were finally included in the qualitative synthesis after meeting the inclusion criteria.Findings: ICT integration was mostly related to increased student engagement, more interactive and learner-centred teaching, and better student performance. Digital learning platforms, multimedia resources, virtual simulations, and mobile applications were the most frequently reported tools and assisted in collaboration and critical thinking. Meanwhile, several obstacles were evident across the studies: a poorly developed infrastructure, insufficient teacher education, poor technical assistance, and socio-economic discrepancies that contribute to the digital divide. Such difficulties were particularly acute in the context of developing countries.Discussion: ICT can truly transform school education, but this transformation requires a lot of planning about how it is done, how well teachers are trained and how institutions are ready to accommodate it. The support of policies, continuous professional training, and investment in the digital infrastructure have become prerequisites. Longitudinal research and context-specific models of integration should be prioritized in future work to aid the sustainable and equitable use.